2021
DOI: 10.3389/fphar.2021.650141
|View full text |Cite
|
Sign up to set email alerts
|

A Scientometric Visualization Analysis for Natural Products on Cancer Research from 2008 to 2020

Abstract: Background: An increasing number of studies have shown that natural products have anti-tumor effects, and it has become a hotspot in cancer research. However, few bibliometric analyses have been examined in this field systematically. The current study aimed to explore the status and provide the developing trends in the natural products on cancer research.Methods: Publications on natural products in cancer research were extracted from the Web of Science core collection database. CiteSpace (5.6.R3) software and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The different colors of nodes represented different years; the different colors of circles from inside to outside indicated the years from 2012 to 2021. The outermost purple ring indicated that the node has very high centeredness and was often regarded as a critical point in a specific domain ( 22 ). The impact factor (IF) and the 2020 edition of Journal Citation Reports (JCR) were both included in the analysis as crucial indications of the research’s scientific worth ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different colors of nodes represented different years; the different colors of circles from inside to outside indicated the years from 2012 to 2021. The outermost purple ring indicated that the node has very high centeredness and was often regarded as a critical point in a specific domain ( 22 ). The impact factor (IF) and the 2020 edition of Journal Citation Reports (JCR) were both included in the analysis as crucial indications of the research’s scientific worth ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…As technology advanced, many technologies drove the development of immunotherapy for CRC. Nanotechnology-based antioxidants and therapeutics were considered the next generation of cancer treatment tools ( 22 ). Duan et al.…”
Section: Introductionmentioning
confidence: 99%
“…The outermost purple ring signifies that the node has a very high centrality and is typically regarded as an important node in a certain area. [11] 3. Results…”
Section: Methodsmentioning
confidence: 99%
“…Analyze References and Keywords Using Burst Detection Burst detection, a powerful tool that captures the sharp increase in the popularity of a references or keywords over a speci c period, is an algorithm developed by Kleinberg [34], and detected research in a eld from macro to micro, from single to the evolutionary trend of diversi cation. This feature is an effective way to identify topics or concepts that have been discussed frequently over a period of time, as well as draw the attention of peer investigators to emerging concepts and future trends.…”
Section: Analyze the Most Frequently Occurring Abstractmentioning
confidence: 99%